Constructing a Damped Spring-mass System with Prescribed Mixed Eigendata. (2017) - Wan, Wenting
Abstract: This paper considers an inverse mixed eigenvalue problem for a damped spring-mass system. The problem of reconstructing the vibration system from its partial physical parameters, complex mode and a real mode of the corresponding undamped system is considered. By solving a kind of quadratic inverse eigenvalue problems, the necessary and sufficient condition for the solvability of the problem is obtained, and a numerical method for solving the problem is proposed. The numerical example shows feasibility of the method.